“Land” as a topic in the book of Psalms? - Bremer, Johannes (Old Testament Essays, 2019)
This essay focuses on land conceptions in the Psalter, dealing with Psalms reflecting on Israel’s history regard land as an integral part of remembrance and YHWH as a powerful and mighty saviour. As he was able to fulfil his promise of land in former times, he is now able to rescue from distress and to grant land for the psalmist’s and subsequent generations. The essay distinguishes between a universal-cosmologic and a particular conception of “land”. Whereas a universal-cosmologic understanding is prevailing, few psalms refer to a particular understanding (i.e., Pss 25; 37; 61; 69). These psalms witness to a conception of “land as reward” in tight connection to a God-fearing life. This thesis of “land as reward” suggests a “metaphorical” application of the concept; further it is accompanied with notions of Zion theology and the theology of poor and poverty.
free